Salmonellosis associated with hepatesplenic Schistosomiasis mansoni: treatment with praziquantel - Shikanai-Yasuda, M. A.; Carvalho, S. A. de; Yasuda, P. H.; Del Negro, G.; Shiroma, M.; Amato Neto, V. (Revista do Instituto de Medicina Tropical de São Paulo, 1985)
Five schistosomiasis patients (hepatesplenic stage) with chronic Salmonella bacteremia were given praziquantel by oral route, single dosis treatment (60 mg/kg). Fever decreased one to three days after the treatment and the patients recovered both from salmonellosis and schistosomiasis. "In vitro" sensitivity test employing Salmonella minnesota, Salmonella dublin, Salmonella panama and Salmonella typhi isolated from patients did not show any activity of praziquantel against these Salmonella species. Patients' sera collected before and 24 hours after treatment were not able to prevent bacterial growth.